Pre-talent management for construction industry - Syed Ali, Sharifah Rahimatul-Hana (2005)
Pre-talent management can be described as the ability to measure the human capital, who are still attending their education and define their performance through an assessment tool designed to quantify this intangible and valuable assets for the construction industry. The objectives of this study are to identify the main component of Personality and Self Direct Search test available in order to assess the actual personality and career interest of the students towards Engineering Code of Ethics. It also produces questionnaires and test questionnaires on samples. It will also analyze the questionnaires using Statistical Method. It is anticipated that the respondent could be placed or guided to choose the right course for their future career. The study shows that, only 10 out 100 respondents show interest in choosing construction engineering as their profession. Only four out of this 10 respondents having a tendency to work according to Engineering Code Of Ethics. The study shows this decision making system may be useful for youngsters in evaluating themselves to be ‘a right person for the right job’